2022
DOI: 10.1001/jamanetworkopen.2021.44959
|View full text |Cite
|
Sign up to set email alerts
|

Association of Exposure to High-risk Antibiotics in Acute Care Hospitals With Multidrug-Resistant Organism Burden in Nursing Homes

Abstract: IMPORTANCELittle is known about the contribution of hospital antibiotic prescribing to multidrugresistant organism (MDRO) burden in nursing homes (NHs). OBJECTIVESTo characterize antibiotic exposures across the NH patient's health care continuum (preceding health care exposure and NH stay) and to investigate whether recent antibiotic exposure is associated with MDRO colonization and room environment contamination at NH study enrollment. DESIGN, SETTING, AND PARTICIPANTS This is a secondary analysis of a prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 56 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…An interesting finding was that antimicrobial exposure in the previous 90 days was associated with decreased odds for death. This is unusual because prior studies have shown that previous antibiotic exposure was associated with acquisition of MDROs, and MDROs have been associated with higher odds of mortality [ 26 , 27 ]. This may be because these patients are in areas with high MDRO exposure and acquired CRPA without traditional risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding was that antimicrobial exposure in the previous 90 days was associated with decreased odds for death. This is unusual because prior studies have shown that previous antibiotic exposure was associated with acquisition of MDROs, and MDROs have been associated with higher odds of mortality [ 26 , 27 ]. This may be because these patients are in areas with high MDRO exposure and acquired CRPA without traditional risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we focused on community-onset sepsis rather than hospital-onset sepsis (where resistant organisms are more prevalent), thus precluding generalizing our findings to all patients with sepsis. We also excluded patients admitted from health care facilities who tend to have higher rates of antibiotic exposure and drug-resistant organisms . Nonetheless, community-onset sepsis accounts for the majority of sepsis cases .…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics were further dichotomized as high- versus low-risk agents for acquisition of ARO or Clostridioides difficile infection (CDI) based on previously validated metrics. 7 High-risk agents consisted of fluoroquinolones, third–fifth generation cephalosporins, β-lactam/β-lactamase combinations, carbapenems, and lincosamines. Clinical infections (urinary tract infection [UTI], pneumonia, skin soft-tissue infection [SSTI], and CDI) were defined based on diagnosis by the treating physician of record at the nursing home.…”
Section: Methodsmentioning
confidence: 99%